1, 2‐Aryl Migration Induced by Amide C−N Bond‐Formation: Reaction of Alkyl Aryl Ketones with Primary Amines Towards α, α‐Diaryl β, γ‐Unsaturated γ‐Lactams. Issue 15 (5th March 2021) - Hu, Rong; Tao, Yigao; Zhang, Xiaofeng; Su, Weiping
Abstract: Rearrangement reactions incorporated into cascade reactions play an important role in rapidly increasing molecular complexity from readily available starting materials. Reported here is a Cu‐catalyzed cascade reaction of α‐(hetero)aryl‐substituted alkyl (hetero)aryl ketones with primary amines that incorporates an unusual 1, 2‐aryl migration induced by amide C−N bond formation to produce a class of structurally novel α, α‐diaryl β, γ‐unsaturated γ‐lactams in generally good‐to‐excellent yields. This cascade reaction has a broad substrate scope with respect to primary amines, allows a wide spectrum of (hetero)aryl groups to smoothly undergo 1, 2‐migration, and tolerates electronically diverse α‐substituents on the (hetero)aryl ring of the ketones. Mechanistically, this 1, 2‐aryl migration may stem from the intramolecular amide C−N bond formation which induces nucleophilic migration of the aryl group from the acyl carbon center to the electrophilic carbon center that is conjugated with the resulting iminium moiety. Abstract : A Cu‐catalyzed dehydrogenative desaturation‐triggered cascade reaction of α‐(hetero)aryl‐substituted alkyl (hetero)aryl ketones with primary amines has been developed to rapidly construct α, α‐diaryl β, γ‐unsaturated γ‐lactams. An intramolecular 1, 2‐(hetero)aryl migration is induced by amide C−N bond formation, providing the products in generally good‐to‐excellent yields across a broad substrate scope with respect to both coupling partners.